(3aUd GdebGd aj gOGjG GdYeGds - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeg GdcGajI heffg GdhGajI hCTgO Cf dG Edg EdG Gddg hMOg dG TQjc dg TgGOI CONQgG LfI ef GdfGQ s
(3BNQgG (B:s
(3JeJ Hefg hcQeg hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1261s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs